Integrasi Konsep Homo Religiosus Dalam Pendidikan Perdamaian: Studi Literatur Pada Konteks Pluralisme - Pratama, Nurul Agna; Asnawi, Naupal (Paedagogie, 2026)
This study aims to analyze the integration of the concept of homo religiosus into peace education within the context of religious pluralism in order to construct a more coherent and contextual conceptual foundation. The research employs a qualitative approach with a systematic literature review design. Data were collected from peer reviewed international journal articles published in the last five years and from the classical work The Sacred and the Profane as a foundational reference in religious anthropology. The collection process involved identification, screening, and final selection based on rigorous inclusion and exclusion criteria. Data were analyzed through qualitative content analysis and iterative conceptual synthesis to formulate an integrative framework. The findings indicate that contemporary peace education is largely instrumental and normatively grounded in human rights and global citizenship paradigms, emphasizing dialogue skills while lacking a robust anthropological foundation. Integrating the concept of homo religiosus shifts the paradigm from a technical orientation toward an anthropological one that recognizes religious consciousness as integral to identity formation. In conclusion, peace education in plural societies becomes more sustainable when grounded in an understanding of human beings as meaning seeking subjects, allowing tolerance to emerge as ethical awareness rather than mere normative compliance.